Professores para a educação ambiental: a interdependência entre saberes na construção da prática docente - Dias, Leci Soares de Moura e (2013)
This study Teachers for Environmental Education: the interdependence between the construction of teaching practice is a qualitative study on the construction of knowledge by teachers focused on environmental education. It was conducted having as subjects six teachers of first grade of elementary schools in public schools of the Municipality of Araponga (MG), located around the State Park of Serra do Brigadeiro, who, between 2002 and 2005, participated of Projeto Veredas, created by an agreement between the Department of Education of Minas Gerais and the Federal University of Viçosa. Based on qualitative research, questionnaires, interviews, and memorials were used, as well as the political-pedagogical document of Projeto Veredas. The tutor who worked with the teachers was also one of the subjects of this research. The discussion presented is based on concerns about the training of teachers and their performance in school, making and remaking their daily lives and that of their students. The knowledge of these teachers is mainly a personal knowledge acquired within family life since childhood, and remain rooted in their practice as part of their life story. They are also knowledge of a different nature, built day by day, with their own teaching experience knowledge that comes from readings provided by textbooks and materials that they resort to develop the teaching-learning process with their students. Such types of knowledge keep a close relationship of interdependence, enabling them to develop pedagogical practices aimed at environmental education